ANALISIS PERAN DINAS SOSIAL TERHADAP PENANGANAN ANAK JALANAN DI KOTA PEKANBARU - Sonia Ningsih; Hambali Hambali; Indra Primahardani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by facts in the field that show the number of street children roaming in Pekanbaru City. Their presence at every intersection of red lights in the middle of the city seems to be a common sight. The formulation of the problem in this study is How is the role of social services to the handling of street children in Pekanbaru City. The purpose of the research is to find out the role of social services to the handling of street children in Pekanbaru City. According to Riau Province Regional Regulation No. 13 of 2013 Paragraph 1 Article 14 concerning the Protection of Basic Rights of Street Children are children whose lives are irregular by spending most of their time outdoors to earn a living on the streets or in public places. This research method is qualitative, the data collection instrument used is observation, interview and documentation. Respondents in this study numbered 7 people, 2 social services and 5 street children. Sampling techniques using Purposive sampling and Accidental sampling. The result of this study is pekanbaru city social service in carrying out its duties has not fully run in accordance with the indicators contained in Riau Regional Regulation No. 13 of 2013 on Basic Rights of Children. Of the 6 indicators (Health, Education, Mental and Spiritual Social Guidance, Social Rehabilitation, Mentoring and Legal Assistance) only four indicators have been implemented, namely Social Guidance, Social Rehabilitation, Mentoring and Social Assistance. Meanwhile, two other indicators, namely Health and Education have been implemented but not yet maximized. This can be seen from the unsuccessful social services handling street children so that they return to the streets.Key Words: Street Children, Social Service, Children's Basic Rights